A cross-sectional study of the association between dynapenia and higher-level functional capacity in daily living in community-dwelling older adults in Japan. Issue 1 (December 2017) - Iwamura, Masaki; Kanauchi, Masao
Abstract Background There are many reports that dynapenia, sarcopenia and frailty each have associations with bodily function or with Instrumental Activities of Daily Living (IADL). However, studies that compare all three conditions and their effects on IADL are lacking. The purpose of this study is to examine associations of sarcopenia, frailty, and dynapenia with IADL. Methods Participants included 123 community-dwelling older adults (31 men, 92 women, ) aged 65 years or older (75.0 ± 5.3 years) who were independent in IADL. In terms of physical function, measurements were performed for muscle mass, grip strength, walking speed, isometric knee extension strength, and unipedal standing. A questionnaire survey was carried out, the Tokyo Metropolitan Institute of Gerontology Index of Competence (TMIG-IC) was administered, and participants were asked about sense of fatigue and amount of activity. Results Dynapenia was associated with classifications of both frailty and sarcopenia. In addition, sarcopenia had a sensitivity and specificity for dynapenia of 33 and 89%, respectively. Frailty had a sensitivity and specificity for dynapenia of 17 and 98%, respectively. Dynapenia was a significant independent related factor for the TMIG-IC (β = −0.21, P  < 0.05). Conclusions Dynapenia, more than sarcopenia or frailty, was related to difficulties with IADL; therefore, assessment of dynapenia should be given greater emphasis in evaluating the physical functioning of older adults.